Promoting EFL Student Teachers’ Life-Long Learning through Microteaching Lesson Study - Fitri Budi Suryani; Dwi Rukmini; Dwi Anggani Linggar Bharati; Rudi Hartono (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
The success of lesson study as an approach for teacher professional development in improving students’ learning has inspired the works on microteaching lesson study which is designed for student teachers in microteaching course. Some studies show that microteaching lesson study brought about positive result to student teachers’ pedagogical ability and content knowledge. However, that microteaching lesson study influences student teachers in their teaching internship, that is the course taken after microteaching where student teachers teach real students in real schools, has not been revealed yet. This study aims at exploring the influence of microteaching lesson study on the English as a Foreign Language (EFL) student teachers in teaching internship and to what extent the influence was to promote the EFL student teachers’ life-long learning to teach. It is a qualitative study with semi-structured group interview as the instrument of the research. The subject of the study was ten EFL student teachers who voluntarily participated in the study from twenty two student teachers. They had enrolled in a microteaching class that applied microteaching lesson study in the sixth semester and then took the teaching internship in the seventh semester. The finding of the study indicates that microteaching lesson study has considerably influences most of the EFL student teachers in gaining life-long learning to teach as they already implemented the steps of microteaching lesson study in their teaching internship initiatively. Finally, this study recommends teacher educators to adapt lesson study in microteaching course that can make the EFL student teachers to keep learning to teach.